Language education policy and multilingual assessment. (4th May 2017) - Gorter, Durk; Cenoz, Jasone
ABSTRACT: In this article, we establish direct links between language policy on the one hand and assessment in multilingual contexts on the other hand. We illustrate the bi-directional relationship with the examples of the USA, Canada, and the Basque Country. That comparison is placed in the context of the changing views about the use of languages in education where a shift can be observed away from an emphasis on separating languages to approaches that more closely suit daily practices of multilinguals. This concerns a shift from language isolation policies in language teaching and assessment towards more holistic approaches that consider language-as-resource and promote the use of the whole linguistic repertoire. However, the implementation of programs based on holistic approaches is limited and application in language assessment modest. Traditions and monolingual ideologies do not give way easily. We show some examples of creative new ways to develop multilingual competence and cross-lingual skills. The assessment of interventions with a multilingual focus point to a potential increase in learning outcomes. Multilingualism is a point of departure because in today's schools, students who speak different languages share the same class, while at the same time learning English (and other languages). We conclude that holistic approaches in language education policy and multilingual assessment need to substitute more traditional approaches.